2011
DOI: 10.1089/ars.2010.3295
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Dietary Selenium Deficiency on Metabolic Phenotypes of Diet-Restricted GPX1-Overexpressing Mice

Abstract: We previously reported a spontaneous development of type 2 diabetes-like phenotypes in glutathione peroxidase-1 (GPX1)-overexpressing (OE) mice. Diet restriction of these mice rescued all their phenotypes, except for hyperinsulinemia and hypersecretion of insulin. This study was to determine whether dietary Se deficiency eliminated these two primary effects of GPX1 overproduction. Forty-seven male OE and wild-type (WT) mice were fed an Se-adequate (0.4 mg Se/kg) or deficient (<0.02 mg Se/kg) diet at 2 to 3 g (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
1
32
1
Order By: Relevance
“…As shown in our previous studies (3,18), the high-selenium diet resulted in a moderate (20-50%) increase in GPX activities in both liver and muscle. Overproduction of GPX activity by Gpx1 overexpression in mice led to type 2 diabetes-like phenotypes, including hyperlipidemia and fatty liver (1,9,19), and the selenium deficiency partially rescued those disorders (9). The high-selenium diet induced gene expression of GPX3 in both liver and muscle and elevated the GPX3 protein in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in our previous studies (3,18), the high-selenium diet resulted in a moderate (20-50%) increase in GPX activities in both liver and muscle. Overproduction of GPX activity by Gpx1 overexpression in mice led to type 2 diabetes-like phenotypes, including hyperlipidemia and fatty liver (1,9,19), and the selenium deficiency partially rescued those disorders (9). The high-selenium diet induced gene expression of GPX3 in both liver and muscle and elevated the GPX3 protein in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19). However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22).…”
Section: Introductionmentioning
confidence: 96%
“…Paradoxically, increased levels of GPx1 in these mice were associated with increased insulin resistance, hyperinsulinemia, hyperglycemia as well as with the development of obesity. It was proposed that these changes in GPx1-overexpressing mice might be explained by elevated pancreatic ␤-cell mass and ␤-cell insulin secretion caused by disrupted reactive oxygen species (ROS) signaling (250,285). By degrading H 2 O 2 , high GPx1 levels have been implicated in both promoting insulin secretion through activation of PDX1 transcription factor-dependent differentiation of pancreatic ␤-cells and increased insulin secretion due to lower levels of UCP2 protein (364).…”
Section: Selenoprotein Functionmentioning
confidence: 99%
“…Mice-The GPx1 overexpressing (OE) mice became obese at 6 months of age, and developed hyperglycemia, hyperinsulinemia, hyperlipidemia, and insulin resistance, along with elevated pancreatic β cell mass, islet insulin secretion, plasma leptin concentration, and hepatic lipogenesis [22][23][24]. Diet restriction (3 vs. 5 g of feed/day) of OE mice from 2 to 6 months of age [55] prevented all their phenotypes except for fasting hyperinsulinemia and hyper-secretion of insulin after glucose stimulation [55].…”
Section: Elevations Of Se Intake and Selenoprotein Expression On Diabmentioning
confidence: 99%
“…While there was a high hope for using antioxidants including Se to prevent and treat diabetes and its complications, a number of recent human trials have actually shown an alarming correlation between high Se intake or body Se status and diabetic risks [15][16][17][18][19][20][21]. Before this revealing, overexpression of GPx1, the "oldest" and most abundant Se-dependent protein, was shown to induce type 2 diabeteslike phenotypes in mice [22][23][24]. After this initial linking of selenoprotein to glucose and lipid metabolism, several new animal studies have provided compelling evidence and mechanism for the pro-diabetic potential of prolonged high Se intakes in different species.…”
Section: Introductionmentioning
confidence: 99%